Living with Koryak Traditions: Playing with Culture in Siberia - Aimar Ventsel (Journal of Ethnology and Folkloristics)
Book review of the publication Alexander D. King, Living with Koryak Traditions: Playing with Culture in Siberia. Lincoln & London: University of Nebraska Press, 2011, 348 pp.